2021
DOI: 10.3390/ma14195658
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride and Hydrogenated Silicon Nitride Thin Films: A Review of Fabrication Methods and Applications

Abstract: Silicon nitride (SiNx) and hydrogenated silicon nitride (SiNx:H) thin films enjoy widespread scientific interest across multiple application fields. Exceptional combination of optical, mechanical, and thermal properties allows for their utilization in several industries, from solar and semiconductor to coated glass production. The wide bandgap (~5.2 eV) of thin films allows for its optoelectronic application, while the SiNx layers could act as passivation antireflective layers or as a host matrix for silicon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…The monomer unit of Kapton (poly(4,4′oxydiphenylene) pyromellitimide) is shown in Figure 1. The films of area 4 × 4 cm 2 were irradiated at room temperature under normal incidence by 1 H, 12 C, 16 O, 28 Si, 59 Co, and 197 Au ions with energies ranging from 1.05 to 48 MeV and an initial charge state between 1+ and 11+. Beam current was measured before and after irradiation using a Faraday cup placed behind the sample position.…”
Section: Ion Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer unit of Kapton (poly(4,4′oxydiphenylene) pyromellitimide) is shown in Figure 1. The films of area 4 × 4 cm 2 were irradiated at room temperature under normal incidence by 1 H, 12 C, 16 O, 28 Si, 59 Co, and 197 Au ions with energies ranging from 1.05 to 48 MeV and an initial charge state between 1+ and 11+. Beam current was measured before and after irradiation using a Faraday cup placed behind the sample position.…”
Section: Ion Irradiationmentioning
confidence: 99%
“…Nanopore detection and sequencing work on the principle of ionic current disruption or variation. Several insulating materials, for example, graphene, [6,10] silicon nitride, [11,12] silicon oxide, [13,14] and polymer membranes [7,[15][16][17] are being studied for nanoscale channel and pore fabrication. Although silicon-based nanopores allow improved miniaturization and possible integration with other electronic devices, the irregular shape of these pores leads to large current noises.…”
Section: Introductionmentioning
confidence: 99%
“…aSiN films are generally known to show a high level of stress and the stress varies with different deposition conditions and methods [38]. Pan et al reported previously that there was a positive correlation between the stress of aSiN films and NH 3 /SiH 4 flow rate ratio in the NH 3 -PECVD process [19].…”
Section: Optical Property Stress and Young's Modulus Measurementsmentioning
confidence: 99%
“…Silicon nitride is the most widely used material as dielectric and passivation layer in microelectronics [1] and as structural material in micro-electro-mechanical systems (MEMS), due to its remarkable optical, chemical, and mechanical properties [2,3]. Silicon nitride thin films also play a vital role in optoelectronics applications due to its high refractive index and transparency in the visible and near-infrared (NIR) region [4,5]. A major application of silicon nitride thin film in the field of optoelectronics is optical waveguide-based biosensors as a planar optical waveguide [6][7][8].…”
Section: Introductionmentioning
confidence: 99%